Clinical response, drug survival and predictors thereof in 432 ankylosing spondylitis patients after switching tumour necrosis factor α inhibitor therapy: results from the Danish nationwide DANBIO registry. Issue 7 (31st August 2012) - Glintborg, Bente; Østergaard, Mikkel; Krogh, Niels Steen; Tarp, Ulrik; Manilo, Natalia; Loft, Anne Gitte Rasmussen; Hansen, Annette; Schlemmer, Annette; Fana, Victoria; Lindegaard, Hanne M; Nordin, Henrik; Rasmussen, Claus; et al.
Abstract : Objective: To investigate frequencies and reasons for switching, treatment responses and drug survival in patients with ankylosing spondylitis (AS) switching tumour-necrosis-factor-α inhibitor (TNFi) treatment in routine clinical care. Methods: AS patients were identified in the Danish nationwide DANBIO registry. Disease activity, treatment responses (50% or 20 mm reduction in Bath AS Disease Activity Index (BASDAI)), duration and rates of drug survival and predictors thereof were studied in patients receiving ≥2 different biological drugs. Results: Of 1436 AS patients starting TNFi treatment, 432 patients (30%) switched to a second and 137 (10%) to a third biological drug. Compared with non-switchers, switchers were more frequently women (33%/22%), had shorter disease duration (3 years/5 years) and higher BASDAI (62(52–76) mm/56(43–69) mm (median(interquartile-range))), Bath AS Functional Index (BASFI) (54(39–71) mm/47(31–65) mm) and visual-analogue-scale (VAS) global, pain and fatigue scores when they started the first TNFi (all p<0.01). Main reason for switching was lack of response (56%). During the first, second and third treatment BAS- and VAS scores had decreased after 6 months' treatment (all p<0.05). Median drug survivals were 3.1, 1.6 and 1.8 years respectively (p<0.001). After 2 years of treatment 52% of switchers and 63% of non-switchers had achieved response (number needed to treat 1.9 and 1.6, respectively, p=0.01). Drug survivals were similar regardless of the reason for switching. Male gender and low BASFI predicted drug survival of the second TNFi. Conclusions: Nearly one-third of AS patients in clinical practice switched biological treatment. Response rates and drug survivals were lower among switchers, however, half of switchers achieved treatment response.